Do males and females respond differently to ocean acidification? An experimental study with the sea urchin Paracentrotus lividus - Marceta T.; Matozzo V.; Alban S.; Badocco D.; Pastore P.; Marin M. G. (Environmental Science and Pollution Research, 2020)
Seawater pH lowering, known as ocean acidification, is considered among the major threats to marine environment. In this study, post-spawning adults of the sea urchin Paracentrotus lividus were maintained at three pH values (8.0, 7.7, 7.4) for 60days. Physiological, biochemical, cellular, behavioural and reproductive responses were evaluated in males and females. Significant differences between sexes were observed, with higher ammonia excretion and lower catalase activity in males. Respiration rate (after 21days), catalase activity in gonads and total coelomocyte count showed the same increasing trend in males and females under low pH. Ammonia excretion, gonadosomatic index and lysozyme activity exhibited opposite responses to low pH, with an increasing trend in males and decreasing in females. Results demonstrated that exposure to low pH could result in different response strategies of male and female sea urchins at a physiological, biochemical and immunological level. Reduced female gonadosomatic index under low pH suggested decreased energy investment in reproduction.